Wastewater treatment process for 2-hydroxy-benzonitril production

By combining composite flocculants, catalysts, and biological treatment in a wastewater treatment process, the problem of removing recalcitrant substances and recovering resources from salicylates production wastewater has been solved, achieving efficient and environmentally friendly wastewater treatment and resource recovery.

CN121342239APending Publication Date: 2026-01-16ANHUI GUANGXIN AGROCHEM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511285730.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-10
Publication Date
2026-01-16

AI Technical Summary

Technical Problem

Existing wastewater treatment technologies for salicylates production suffer from problems such as difficulty in effectively removing colloidal pollutants, low ozone utilization, high operating costs, serious resource waste, and a lack of awareness regarding resource recycling.

Method used

A composite flocculant is used for pretreatment, combined with a composite catalyst and immobilized biological treatment, followed by activated carbon adsorption to recover salicylic acid. The specific steps include pH adjustment, ozone catalytic oxidation, immobilized biological treatment and activated carbon adsorption.

Benefits of technology

It achieves efficient removal of recalcitrant organic matter from wastewater, reduces sludge production and secondary pollution, recovers valuable salicylic acid resources, lowers treatment costs, and meets environmental and economic requirements.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of wastewater treatment, and particularly relates to a wastewater treatment process for 2-hydroxy-benzonitril production. The 2-hydroxy-benzonitril production wastewater treatment process has remarkable technical advantages and environmental economic value, the amphoteric chitosan-carboxymethyl starch grafted flocculant efficiently removes multiple types of colloidal pollutants under the weak alkaline condition through the synergistic effect of charge neutralization and adsorption bridging; during the catalytic oxidation reaction, La2O3 stabilizes the carrier structure and modulates the electron distribution of an active center, so that ozone and H2O2 are promoted to generate a large number of high-activity free radicals, cyano groups and benzene rings are efficiently broken, the biodegradability of wastewater is greatly improved, and the toxicity is eliminated; a polyurethane foam-sodium alginate dual immobilization technology is adopted to construct a stable microenvironment for the flora, and P.putida and B.subtilis synergistically secrete functional enzymes to degrade nitriles and phenols; and finally, activated carbon adsorption recovery is carried out, the green circular economy requirement is met, and efficient treatment and resource value-added benefits are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of wastewater treatment, and particularly relates to a wastewater treatment process for salicylanilide production. BACKGROUND

[0002] Salicylanilide is an important intermediate of chemical products such as pesticides, liquid crystal materials and medicines, and plays a key role in the synthesis of a new type of high-efficiency broad-spectrum strobilurin fungicide azoxystrobin. A large amount of organic wastewater is generated in the production process, and the wastewater contains difficult-to-degrade pollutants such as organic cyanide and phenolic derivatives, and has characteristics such as high chemical oxygen demand (COD), strong biological toxicity and poor biodegradability.

[0003] The existing treatment technology has significant limitations in dealing with salicylanilide production wastewater: (1) In the pretreatment stage, although the traditional inorganic flocculant has low cost, it has problems such as large dosage, high sludge yield and metal ion residue, especially in low temperature environment, the flocculation effect is greatly reduced, and it is difficult to effectively remove colloidal pollutants in wastewater. (2) In the deep oxidation link, the single ozone oxidation technology has low ozone utilization rate, limited mineralization rate, low removal rate of complex organic cyanide, and high operating cost; while the traditional Fenton method has strong oxidation ability, but it needs to maintain an acidic pH environment, and generates a large amount of iron-containing sludge, which is easy to cause secondary pollution. In addition, the existing process generally lacks resource recycling awareness. Salicylic acid and other intermediate products with recycling value are generated in the degradation process of salicylanilide wastewater, but the traditional process adopts direct discharge or incineration treatment, which not only causes resource waste, but also increases environmental protection pressure.

[0004] Therefore, it is urgent to develop a salicylanilide production wastewater treatment process that can specifically degrade difficult-to-degrade organic matter, reduce secondary pollution and realize resource recycling, so as to meet the environmental protection requirements and enterprise cost reduction needs. SUMMARY

[0005] The purpose of the present application is to provide a wastewater treatment process for salicylanilide production to solve the existing problems.

[0006] The present application is realized by the following technical scheme:

[0007] A wastewater treatment process for salicylanilide production, comprising the following steps:

[0008] S1, adjusting the pH of salicylanilide production wastewater to 8.2-8.8 first, then adding a composite flocculant, stirring and then standing and precipitating;

[0009] S2, introducing the supernatant after standing and precipitating in S1 into a reactor containing a composite catalyst, and introducing ozone and a small amount of H2O2 for catalytic oxidation reaction;

[0010] S3, introducing the oxidized wastewater into a fixed bed bioreactor filled with immobilized bacteria to perform immobilized biological treatment;

[0011] S4, passing the water treated by the biological treatment into an activated carbon adsorption column, eluting the saturated activated carbon with dilute ethanol, and evaporating and crystallizing the eluent to obtain salicylic acid crystals.

[0012] Further, the NaOH or Na2CO3 used for adjusting the pH in step S1;

[0013] The stirring speed is 150-200 rpm, and the stirring time is 20-30 min.

[0014] Further, the dosage of the composite flocculant in step S1 is 150-200 mg / L, and the preparation method of the composite flocculant is as follows: the carboxymethyl starch aqueous solution is added to a four-necked flask, heated to 55-60°C under the condition of a stirring speed of 150-200 rpm, then the chitosan acetic acid solution is added dropwise at a speed of 3-4 mL / min, after the dropwise addition is completed, the stirring is continued for 30-35 min, then the initiator solution is added dropwise at a speed of 1-1.5 mL / min, after the dropwise addition is completed, the temperature is raised to 65-70°C, and the grafting reaction is carried out under the condition of temperature and stirring for 2.5-3 h, after the reaction is completed, the reaction solution is poured into 95% ethanol, the precipitate is separated out, and after standing for 1 h, the precipitate is collected by suction filtration, washed with 70% ethanol for 2-3 times, then vacuum dried at 55-60°C for 6-8 h, and crushed through a 60-mesh sieve;

[0015] The volume ratio of the carboxymethyl starch aqueous solution, the chitosan acetic acid solution and the initiator solution is 50:33:1.

[0016] Further, the preparation of the carboxymethyl starch aqueous solution comprises the following steps:

[0017] (1) corn starch is added to 95% ethanol according to a solid-liquid ratio of 1:2-3, uniformly dispersed at 100-150 rpm, then a 20% NaOH solution is added dropwise (the dropwise addition speed is 2-3 mL / min, and the volume ratio of the NaOH solution to the ethanol is 1:2-3), after the dropwise addition is completed, the temperature is raised to 30-35°C, and after stirring and keeping the temperature for 1.5-2 h, an ethyl chloroacetate solution is added dropwise (the dropwise addition speed is 1-2 mL / min, and the dropwise addition amount of the ethyl chloroacetate solution is 0.16-0.2 times the total volume of the NaOH solution and the ethanol solution), after the dropwise addition is completed, the temperature is raised to 55-60°C, and the etherification is carried out under the condition of temperature and stirring for 3-4 h;

[0018] The preparation method of the ethyl chloroacetate solution is as follows: chloroacetic acid is dissolved in 95% ethanol according to a solid-liquid ratio of 1:1-1.5 to obtain the ethyl chloroacetate solution;

[0019] During the stirring etherification, sample every 30 min, determine the degree of substitution of carboxymethyl starch by potential titration method, ensure that the final degree of substitution reaches 0.8~1;

[0020] (2) After the etherification reaction is completed, 95% ethanol is added to the system, and after stirring for 10 min, the carboxymethyl starch precipitate is separated by suction filtration, and the precipitate is washed with 70% ethanol until there is no Cl - in the washing liquid, and then the powder is crushed to 80 mesh after vacuum drying at 60~65℃ for 4~6h to obtain a powdery carboxymethyl starch;

[0021] (3) The powdery carboxymethyl starch is prepared into a carboxymethyl starch aqueous solution with a concentration of 100g / L with deionized water for standby.

[0022] Further, the preparation method of the chitosan acetic acid solution is as follows: chitosan is added to a 40% mass fraction NaOH solution (solid-liquid ratio 1:10), stirred and treated in a 80~85℃ constant temperature water bath for 4~6h, washed to neutral with deionized water after treatment, and vacuum dried to constant weight at 60~65℃ to obtain refined chitosan; the refined chitosan is prepared into a chitosan acetic acid solution with a concentration of 50g / L with a 2% mass fraction acetic acid solution;

[0023] Further, the preparation method of the initiator solution is as follows: sodium persulfate is prepared into an initiator solution with a concentration of 60~75g / L with deionized water;

[0024] Further, the preparation of the composite catalyst in step S2 includes the following steps:

[0025] S201, mesoporous γ-Al2O3 carrier is added to a plasma treatment instrument, an air medium is adopted, the power is 150W, the vacuum degree is-0.06MPa, and the treatment is carried out for 15~20min; the treated carrier is placed in a 100~110℃ air drying oven for drying for 2.5~3.5h to obtain an activated carrier;

[0026] S202, lanthanum nitrate is added to deionized water, and stirred at 40~45℃ until completely dissolved to obtain a La impregnation solution; 1 / 3 mass of the above activated carrier is taken, the La impregnation solution is added dropwise to the activated carrier according to a liquid-solid ratio of 1:1, and the mixture is placed at room temperature for 1.5~2.5h and then air dried at 60℃ for 2~2.5h to obtain a La-loaded carrier precursor;

[0027] S203. Copper nitrate and manganese nitrate are added to deionized water and stirred at 45~50℃ until completely dissolved to obtain Cu-Mn mixed impregnation solution. Using the equal volume impregnation method, the Cu-Mn mixed impregnation solution is added dropwise to the mixture of the remaining 2 / 3 mass of the activated support and the La-loaded support precursor at a liquid-solid ratio of 7:6, while stirring (120 rpm). After the addition is complete, it is allowed to stand at room temperature for 3~3.5 h to obtain Cu-Mn-La / γ-Al2O3 support precursor.

[0028] Total metal loading 8~10%, Cu:Mn:La=3:2:1;

[0029] S204. Melamine is added to deionized water at a solid-liquid ratio of 1:12~14, and stirred at 80~85℃ for 1h to obtain a suspension. The above Cu-Mn-La / γ-Al2O3 support precursor is added to the suspension, stirred at 50~55℃ for 1~2h, dried at 60℃ for 1.5~2h, and then dried at 90℃ for 3~4h.

[0030] S205, after drying, is placed in a muffle furnace and heated to 200℃ at a rate of 2℃ / min under air atmosphere, and held at that temperature for 1 hour. Then, it is heated to 350℃ at a rate of 3℃ / min and held at that temperature for 2.5 hours. Next, it is heated to 480℃ at a rate of 4℃ / min and held at that temperature for 3.5 hours. Finally, it is cooled to a constant temperature at a rate of 5℃ / min and ground until the particle size is 0.5~1mm.

[0031] Furthermore, the amount of ozone added in step S2 is 50~60 mg / L, and the amount of trace H2O2 added is 20~30 mg / L;

[0032] The catalytic oxidation time is 45-55 min, and the reaction temperature is 25-35℃.

[0033] Further, the method for preparing the immobilized bacterial agent in step S3 is as follows: Pseudomonas and Bacillus mixed bacteria are immobilized on a porous foam carrier, with a viable cell density of 102. 9 ~10 10 CFU / g;

[0034] The temperature is controlled at 25~35℃ and the hydraulic retention time is 6~8h during the immobilized biological treatment.

[0035] Furthermore, the preparation of the immobilized bacterial agent includes the following steps:

[0036] S301. After washing the polyurethane foam with anhydrous ethanol and sterile water in sequence, it is then immersed in 0.1 mol / L hydrochloric acid solution for 2-2.5 h, then immersed in 0.1 mol / L sodium hydroxide solution for 2-2.5 h, and finally rinsed with sterile water until neutral. After that, it is autoclaved at 121℃ for 25-30 min and dried at 50℃ to constant weight for later use.

[0037] S302. Using LB modified medium (containing 2 g / L phenol), Pseudomonas putida (ATCC 49128) and Bacillus subtilis (CGMCC 1.3358) were activated to OD600 = 1.2~1.5 and OD600 = 1.0~1.2 respectively. The two bacterial solutions were then mixed at a volume ratio of 3:2 and stirred evenly to obtain a mixed bacterial solution.

[0038] S303. Add the polyurethane foam treated in step S301 to the mixed bacterial solution at a solid-liquid ratio of 1:5. Shake and adsorb at 28~30℃ and 100~120rpm for 1.5~2.5h. Pour off the supernatant, add fresh mixed bacterial solution, transfer to a vacuum drying oven, and let stand at -0.06MPa and 28℃ for 1~1.5h. Remove the polyurethane foam and let it drain naturally.

[0039] S304. Dissolve sodium alginate in sterile water, stir at 60°C until dissolved, cool and add calcium chloride, stir until completely dissolved to obtain a crosslinking solution. The concentration of sodium alginate is 2% and the concentration of calcium chloride is 5%. Immerse the polyurethane foam adsorbed in step S303 into the crosslinking solution, let it stand at 25°C for 30-40 minutes, rinse with sterile water 2-3 times, and dry with forced air at 60°C for 1 hour.

[0040] S305. Then place in a sterile incubator, add LB modified medium (containing 2 g / L phenol), and incubate at 28°C for 48-56 hours. During this period, replace the medium with fresh medium every 12 hours, and monitor the viable cell density by plate counting until it reaches 10⁻⁶. 9 ~10 10 CFU / g.

[0041] Furthermore, in step S4, the activated carbon in the activated carbon adsorption column has a particle size of 0.5~1mm, an adsorption flow rate of 1~2BV / h, and an elution ethanol concentration of 35%. The eluent is evaporated and crystallized to obtain salicylic acid crystals.

[0042] The present invention has the following advantages over the prior art:

[0043] 1. The chitosan-carboxymethyl starch graft copolymer flocculant prepared by this invention has cationic amino groups (-NH4+) on its molecular chain. 3+ ) and anionic carboxyl groups (-COO)- This forms a unique amphoteric structure. Under weakly alkaline conditions, the flocculant can efficiently remove colloidal phenols, nitriles, and suspended solids with varying charges from wastewater through the synergistic effects of charge neutralization, adsorption bridging, and netting and sweeping. This overcomes the shortcomings of traditional inorganic flocculants, such as high sludge production and low efficiency at low temperatures, providing a good foundation for subsequent advanced treatment units.

[0044] 2. In the Cu-Mn-La / γ-Al2O3 composite catalyst constructed in this invention, the incorporation of La2O3 effectively stabilizes the mesoporous structure of the γ-Al2O3 support and modulates the electron distribution of the Cu and Mn active centers. A rapid redox cycle exists between Cu and Mn oxides, which greatly promotes the decomposition of ozone molecules and hydrogen peroxide, generating highly reactive species such as hydroxyl radicals and superoxide radicals far exceeding the amount produced by ozone oxidation alone. These strong oxidizing radicals can non-selectively attack the cyano groups of organic cyanides and the benzene ring structures of phenolic substances in wastewater, breaking them down into small-molecule organic acids, carbon dioxide, and water. This significantly improves the biodegradability of wastewater and eliminates its biotoxicity, clearing obstacles for biological treatment.

[0045] 3. In the immobilized biological treatment stage, a dual immobilization method combining polyurethane foam adsorption and sodium alginate-calcium chloride gel encapsulation was employed to construct a stable micro-ecological environment for the functional microbial community. The gel layer effectively blocked the direct impact of residual toxins and oxidants on the bacteria and reduced bacterial loss. *Pseudomonas putida* and *Bacillus subtilis* formed a functional complement; *P. putida* secreted nitrile hydrolase, specifically degrading residual nitrile substances; *B. subtilis* secreted extracellular enzymes such as phenol oxidase to degrade phenolic derivatives, and its spore structure endowed the entire microbial community with extremely strong environmental resistance. The synergy between the two ensured the stable operation of the biological treatment system under high-load conditions and the deep removal of pollutants.

[0046] 4. This invention utilizes the large specific surface area and abundant surface functional groups of activated carbon to achieve highly selective adsorption of salicylic acid (containing benzene rings and carboxyl groups), an intermediate product of oxidative degradation, through various interactions such as hydrophobic interactions, π-π stacking, and hydrogen bonding. Dilute ethanol is used as the eluent, and salicylic acid is efficiently desorbed through competitive adsorption. The eluent can be evaporated and crystallized to recover high-purity salicylic acid, turning waste into treasure and directly offsetting part of the treatment costs. The effluent from the biological treatment can be directly reused after purification by activated carbon adsorption. The eluent ethanol can be recovered and recycled through evaporation and condensation. The final effluent from the entire process is only a small amount of crystallization mother liquor, greatly reducing secondary pollution and fresh water consumption, meeting the requirements of green chemistry and a circular economy. Detailed Implementation

[0047] To further explain the present invention, the following specific embodiments are described.

[0048] The *Pseudomonas putida* used in this invention is *Pseudomonas putida*, ATCC 49128; and *Bacillus subtilis* is *Bacillus subtilis*, CGMCC 1.3358.

[0049] Example 1

[0050] A wastewater treatment process for salicylnitrile production includes the following steps:

[0051] S1. Adjust the pH of the salicylates production wastewater to 8.2 with NaOH or Na2CO3, then add the composite flocculant and stir at 150 rpm for 20 min before allowing it to settle.

[0052] The dosage of the composite flocculant is 150 mg / L, and the preparation of the composite flocculant includes the following steps:

[0053] S101. Add chitosan to a 40% NaOH solution (solid-liquid ratio 1:10, g:mL), stir in an 80℃ constant temperature water bath for 4 hours, wash with deionized water until neutral, and vacuum dry at 60℃ to constant weight to obtain refined chitosan.

[0054] S102. Add corn starch to 95% ethanol at a solid-liquid ratio of 1:2 (g:mL), disperse evenly at 100rpm, then add 20% NaOH solution (dropping rate of 2mL / min, volume ratio of NaOH solution to ethanol of 1:2). After the addition is complete, raise the temperature to 30℃, keep warm and stir for 1.5h, then add chloroacetic acid ethanol solution (dropping rate of 1mL / min, the amount of chloroacetic acid ethanol solution added is 0.16 times the total volume of NaOH solution and ethanol solution). After the addition is complete, raise the temperature to 55℃, keep warm and stir for etherification for 3h.

[0055] The method for preparing the chloroacetic acid ethanol solution is as follows: dissolve chloroacetic acid in 95% ethanol at a solid-liquid ratio of 1:1 (g:mL).

[0056] Samples were taken every 30 minutes during the stirring etherification process, and the degree of substitution of carboxymethyl starch was determined by potentiometric titration to ensure that the final degree of substitution reached 0.8.

[0057] S103. After the etherification reaction is complete, add 95% ethanol to the system, stir for 10 min, and let stand for 30 min. Carboxymethyl starch precipitate will precipitate. Filter to separate the precipitate, and wash with 70% ethanol until no Cl is found in the washing solution. -Then, after vacuum drying at 60°C for 4 hours, it is pulverized and passed through an 80-mesh sieve to obtain powdered carboxymethyl starch;

[0058] S104. Prepare a chitosan acetic acid solution with a concentration of 50 g / L by using a 2% (w / w) acetic acid solution.

[0059] The powdered carboxymethyl starch was prepared into a carboxymethyl starch aqueous solution with a concentration of 100 g / L using deionized water.

[0060] Sodium persulfate was prepared into an initiator solution of 60 g / L using deionized water;

[0061] A carboxymethyl starch aqueous solution was added to a four-necked flask, and the temperature was raised to 55°C at 150 rpm. Then, chitosan acetic acid solution was added dropwise at a rate of 3 mL / min. After the addition was complete, the mixture was stirred for 30 min. Then, an initiator solution was added dropwise at a rate of 1 mL / min. After the addition was complete, the temperature was raised to 65°C, and the mixture was stirred for 2.5 h to carry out the grafting reaction. After the reaction was completed, the reaction solution was poured into 95% ethanol, and a precipitate was formed. After standing for 1 h, the precipitate was filtered, collected, washed twice with 70% ethanol, and then vacuum dried at 55°C for 6 h. The precipitate was then pulverized and passed through a 60-mesh sieve.

[0062] S2. The supernatant after settling in S1 is introduced into a reactor containing a composite catalyst, and ozone and trace amounts of H2O2 are introduced. The amount of ozone added is 50 mg / L, and the amount of trace amounts of H2O2 added is 20 mg / L. Catalytic oxidation is carried out at 25°C for 45 min.

[0063] The ozone dosage is 50 mg / L, and the trace H2O2 dosage is 20 mg / L;

[0064] The preparation of the composite catalyst includes the following steps:

[0065] S201, Mesoporous γ-Al2O3 support (particle size 0.5~1mm, specific surface area 200~280m²) 2 / g, mesopore size 5~12nm, purity ≥99%) was added to the plasma treatment instrument, using air medium, power 150W, vacuum degree -0.06MPa, and treatment for 15min. The treated carrier was then placed in a 100℃ forced-air drying oven and dried for 2.5h to obtain the activated carrier.

[0066] S202. Lanthanum nitrate was added to deionized water and stirred at 40°C until completely dissolved to obtain a La impregnation solution. Using the equal volume impregnation method, 1 / 3 of the above activated support was taken and the La impregnation solution was added dropwise to the activated support at a liquid-solid ratio of 1:1 (mL:g). After standing at room temperature for 1.5 h, the solution was dried at 60°C for 2 h to obtain the La-loaded support precursor.

[0067] S203. Copper nitrate and manganese nitrate were added to deionized water and stirred at 45°C until completely dissolved to obtain a Cu-Mn mixed impregnation solution. Using the equal volume impregnation method, the Cu-Mn mixed impregnation solution was added dropwise to the remaining 2 / 3 mass of the mixture of activated support and La-loaded support precursor at a liquid-solid ratio of 7:6 (mL:g). The mixture was stirred while being added dropwise (120 rpm). After the addition was completed, the mixture was allowed to stand at room temperature for 3 h to obtain the Cu-Mn-La / γ-Al2O3 support precursor.

[0068] Total metal loading 8%, Cu:Mn:La = 3:2:1;

[0069] S204. Melamine was added to deionized water at a solid-liquid ratio of 1:12 (g:mL), and the mixture was stirred at 80°C for 1 h to obtain a suspension. The Cu-Mn-La / γ-Al2O3 support precursor was added to the suspension, and the mixture was stirred at 50°C for 1 h, dried at 60°C for 1.5 h, and then dried at 90°C for 3 h.

[0070] S205, after drying, is placed in a muffle furnace and heated to 200℃ at a rate of 2℃ / min under air atmosphere, held at the temperature for 1 hour, then heated to 350℃ at a rate of 3℃ / min, held at the temperature for 2.5 hours, then heated to 480℃ at a rate of 4℃ / min, held at the temperature for 3.5 hours, and finally cooled to the constant temperature at a rate of 5℃ / min. The particles are then ground to a particle size of 0.5 mm.

[0071] S3. Introduce the oxidized wastewater into a fixed-bed bioreactor, fill it with immobilized bacterial agent, and carry out immobilized biological treatment. Control the temperature at 25℃ and the hydraulic retention time at 6h.

[0072] The method for preparing the immobilized bacterial agent is as follows: a mixture of Pseudomonas and Bacillus bacteria is immobilized on a porous foam carrier, with a viable cell density of 10⁻⁶. 9 CFU / g.

[0073] Specifically:

[0074] S302 The polyurethane foam is washed sequentially with anhydrous ethanol and sterile water, then soaked in 0.1 mol / L hydrochloric acid solution for 2 hours, then soaked in 0.1 mol / L sodium hydroxide solution for 2 hours, and finally rinsed with sterile water until neutral. After that, it is autoclaved at 121°C for 25 minutes and dried at 50°C to constant weight for later use.

[0075] S302. Pseudomonas putida and Bacillus subtilis were activated to OD600=1.2 and OD600=1.0 respectively using LB modified medium (containing 2g / L phenol). The two bacterial solutions were then mixed at a volume ratio of 3:2 and stirred evenly to obtain a mixed bacterial solution.

[0076] S303. Add the polyurethane foam treated in step S301 to the mixed bacterial solution at a solid-liquid ratio of 1:5. Shake and adsorb at 28°C and 100 rpm for 1.5 hours. Pour off the supernatant, add fresh mixed bacterial solution, transfer to a vacuum drying oven, and let stand at -0.06 MPa and 28°C for 1 hour. Take out the polyurethane foam and let it drain naturally.

[0077] S304. Dissolve sodium alginate in sterile water, stir at 60°C until dissolved, cool and add calcium chloride, stir until completely dissolved to obtain a crosslinking solution. The concentration of sodium alginate is 2% and the concentration of calcium chloride is 5%. Immerse the polyurethane foam adsorbed in step S303 into the crosslinking solution, let it stand at 25°C for 30 minutes, rinse with sterile water for 2 hours, and then dry with a forced air at 60°C for 1 hour.

[0078] S305. Then place in a sterile incubator, add LB modified medium (containing 2 g / L phenol), and incubate at 28°C for 48 hours. During this period, replace the medium with fresh medium every 12 hours, and monitor the viable cell density by plate counting until it reaches 10⁻⁶. 9 CFU / g;

[0079] S4. Pass the biologically treated effluent into an activated carbon adsorption column. After adsorption saturation, elute with dilute ethanol. The activated carbon particle size is 0.5 mm, the adsorption flow rate is 1 BV / h, and the elution ethanol concentration is 3%. Evaporate the eluent to obtain salicylic acid crystals.

[0080] Example 2

[0081] A wastewater treatment process for salicylnitrile production includes the following steps:

[0082] S1. Adjust the pH of the salicylates production wastewater to 8.5 with NaOH or Na2CO3, then add the composite flocculant and stir at 180 rpm for 25 min before allowing it to settle.

[0083] The dosage of the composite flocculant is 170 mg / L, and the preparation of the composite flocculant includes the following steps:

[0084] S101. Add chitosan to a 40% NaOH solution (solid-liquid ratio 1:10), stir in an 82℃ constant temperature water bath for 5 hours, wash with deionized water until neutral, and vacuum dry at 62℃ to constant weight to obtain refined chitosan.

[0085] S102. Corn starch was added to 95% ethanol at a solid-liquid ratio of 1:2.5 and dispersed evenly at 120 rpm. Then, a 20% NaOH solution was added dropwise (dropping rate of 2.5 mL / min, volume ratio of NaOH solution to ethanol of 1:2.5). After the addition was complete, the temperature was raised to 32℃ and stirred for 1.7 h. Then, a chloroacetic acid ethanol solution was added dropwise (dropping rate of 1.5 mL / min, the amount of chloroacetic acid ethanol solution added was 0.18 times the total volume of NaOH solution and ethanol solution). After the addition was complete, the temperature was raised to 57℃ and stirred for etherification for 3.5 h.

[0086] The method for preparing the chloroacetic acid ethanol solution is as follows: dissolve chloroacetic acid in 95% ethanol at a solid-liquid ratio of 1:1.2.

[0087] Samples were taken every 30 minutes during the stirring etherification process, and the degree of substitution of carboxymethyl starch was determined by potentiometric titration to ensure that the final degree of substitution reached 0.9.

[0088] S103. After the etherification reaction is complete, add 95% ethanol to the system, stir for 10 min, and let stand for 35 min to precipitate carboxymethyl starch. Filter to separate the precipitate, and wash with 70% ethanol until no Cl is found in the washing solution. - Then, after vacuum drying at 62°C for 5 hours, it was pulverized and passed through an 80-mesh sieve to obtain powdered carboxymethyl starch.

[0089] S104. Prepare a chitosan acetic acid solution with a concentration of 50 g / L by using a 2% (w / w) acetic acid solution.

[0090] The powdered carboxymethyl starch was prepared into a carboxymethyl starch aqueous solution with a concentration of 100 g / L using deionized water.

[0091] Sodium persulfate was prepared into an initiator solution of 68 g / L using deionized water;

[0092] A carboxymethyl starch aqueous solution was added to a four-necked flask, and the temperature was raised to 58°C at 170 rpm. Then, chitosan acetic acid solution was added dropwise at a rate of 3.5 mL / min. After the addition was complete, the mixture was stirred for 32 min. Then, initiator solution was added dropwise at a rate of 1.2 mL / min. After the addition was complete, the temperature was raised to 67°C, and the mixture was stirred for 2.7 h to carry out the grafting reaction. After the reaction was completed, the reaction solution was poured into 95% ethanol, and a precipitate was formed. After standing for 1 h, the precipitate was filtered, collected, washed twice with 70% ethanol, and then vacuum dried at 58°C for 7 h. The precipitate was then pulverized and passed through a 60-mesh sieve.

[0093] S2. The supernatant after settling in S1 is introduced into a reactor containing a composite catalyst, and ozone and trace amounts of H2O2 are introduced. The amount of ozone added is 55 mg / L, and the amount of trace amounts of H2O2 added is 25 mg / L. Catalytic oxidation is carried out at 30°C for 50 min.

[0094] The ozone dosage is 55 mg / L, and the trace H2O2 dosage is 25 mg / L;

[0095] The preparation of the composite catalyst includes the following steps:

[0096] S201, Mesoporous γ-Al2O3 support (particle size 0.5~1mm, specific surface area 200~280m²) 2 / g, mesopore size 5~12nm, purity ≥99%) was added to the plasma treatment instrument, using air medium, power 150W, vacuum degree -0.06MPa, and treatment for 17min. The treated support was then placed in a 105℃ forced-air drying oven and dried for 3h to obtain the activated support.

[0097] S202. Lanthanum nitrate was added to deionized water and stirred at 42°C until completely dissolved to obtain a La impregnation solution. Using the equal volume impregnation method, 1 / 3 of the above activated support was taken and the La impregnation solution was added dropwise to the activated support at a liquid-solid ratio of 1:1. After standing at room temperature for 2 hours, the solution was dried at 60°C for 2.2 hours to obtain the La-loaded support precursor.

[0098] S203. Copper nitrate and manganese nitrate were added to deionized water and stirred at 48°C until completely dissolved to obtain a Cu-Mn mixed impregnation solution. Using the equal volume impregnation method, the Cu-Mn mixed impregnation solution was added dropwise to the remaining 2 / 3 mass of the mixture of activated support and La-loaded support precursor at a liquid-solid ratio of 7:6, while stirring (120 rpm). After the addition was completed, the mixture was allowed to stand at room temperature for 3.2 h to obtain the Cu-Mn-La / γ-Al2O3 support precursor.

[0099] Total metal loading 9%, Cu:Mn:La = 3:2:1;

[0100] S204. Melamine was added to deionized water at a solid-liquid ratio of 1:13 and stirred at 82°C for 1 h to obtain a suspension. The above Cu-Mn-La / γ-Al2O3 support precursor was added to the suspension and stirred at 52°C for 1.5 h. Then, it was dried at 60°C for 1.8 h and then dried at 90°C for 3.5 h.

[0101] S205, after drying, is placed in a muffle furnace and heated to 200℃ at a rate of 2℃ / min under air atmosphere, and held at that temperature for 1 hour. Then, it is heated to 350℃ at a rate of 3℃ / min and held at that temperature for 2.5 hours. Next, it is heated to 480℃ at a rate of 4℃ / min and held at that temperature for 3.5 hours. Finally, it is cooled to a constant temperature at a rate of 5℃ / min and ground until the particle size is 0.7 mm.

[0102] S3. Introduce the oxidized wastewater into a fixed-bed bioreactor, fill it with immobilized bacterial agent, and carry out immobilized biological treatment. Control the temperature at 30℃ and the hydraulic retention time at 7h.

[0103] The method for preparing the immobilized bacterial agent is as follows: a mixture of Pseudomonas and Bacillus bacteria is immobilized on a porous foam carrier, with a viable cell density of 10⁻⁶. 9 CFU / g.

[0104] Specifically:

[0105] S302 The polyurethane foam was washed sequentially with anhydrous ethanol and sterile water, then immersed in 0.1 mol / L hydrochloric acid solution for 2.2 h, then immersed in 0.1 mol / L sodium hydroxide solution for 2.2 h, and finally rinsed with sterile water until neutral. After that, it was autoclaved at 121 °C for 28 min and dried at 50 °C to constant weight for later use.

[0106] S302. Pseudomonas putida and Bacillus subtilis were activated to OD600=1.3 and OD600=1.1 respectively using LB modified medium (containing 2g / L phenol). The two bacterial solutions were then mixed at a volume ratio of 3:2 and stirred evenly to obtain a mixed bacterial solution.

[0107] S303. Add the polyurethane foam treated in step S301 to the mixed bacterial solution at a solid-liquid ratio of 1:5. Shake and adsorb at 29°C and 110 rpm for 2 hours. Pour off the supernatant, add fresh mixed bacterial solution, transfer to a vacuum drying oven, and let stand at -0.06 MPa and 28°C for 1.2 hours. Take out the polyurethane foam and let it drain naturally.

[0108] S304. Dissolve sodium alginate in sterile water, stir at 60°C until dissolved, cool and add calcium chloride, stir until completely dissolved to obtain a crosslinking solution. The concentration of sodium alginate is 2% and the concentration of calcium chloride is 5%. Immerse the polyurethane foam adsorbed in step S303 into the crosslinking solution, stand at 25°C for 35 minutes, rinse with sterile water for 2 hours, and dry with forced air at 60°C for 1 hour.

[0109] S305. Then place in a sterile incubator, add LB modified medium (containing 2 g / L phenol), and incubate at 28°C for 52 hours. During this period, replace the medium with fresh medium every 12 hours, and monitor the viable cell density by plate counting until it reaches 10⁻⁶. 9 CFU / g;

[0110] S4. Pass the biologically treated effluent into an activated carbon adsorption column. After adsorption saturation, elute with dilute ethanol. The activated carbon particle size is 0.7 mm, the adsorption flow rate is 1.5 BV / h, and the elution ethanol concentration is 4%. Evaporate the eluent to obtain salicylic acid crystals.

[0111] Example 3

[0112] A wastewater treatment process for salicylnitrile production includes the following steps:

[0113] S1. Adjust the pH of the salicylates production wastewater to 8.8 with NaOH or Na2CO3, then add the composite flocculant and stir for 30 minutes at 200 rpm, followed by static sedimentation.

[0114] The dosage of the composite flocculant is 200 mg / L, and the preparation of the composite flocculant includes the following steps:

[0115] S101. Add chitosan to a 40% NaOH solution (solid-liquid ratio 1:10), stir in an 85℃ constant temperature water bath for 6 hours, wash with deionized water until neutral, and vacuum dry at 65℃ to constant weight to obtain refined chitosan.

[0116] S102. Add corn starch to 95% ethanol at a solid-liquid ratio of 1:3. After dispersing evenly at 150 rpm, add 20% NaOH solution (dropping rate of 3 mL / min, volume ratio of NaOH solution to ethanol of 1:3). After the addition is complete, raise the temperature to 35℃ and stir for 2 hours. Then add chloroacetic acid ethanol solution (dropping rate of 2 mL / min, the amount of chloroacetic acid ethanol solution added is 0.2 times the total volume of NaOH solution and ethanol solution). After the addition is complete, raise the temperature to 60℃ and stir for etherification for 4 hours.

[0117] The method for preparing the chloroacetic acid ethanol solution is as follows: dissolve chloroacetic acid in 95% ethanol at a solid-liquid ratio of 1:1.5.

[0118] Samples were taken every 30 minutes during the stirring etherification process, and the degree of substitution of carboxymethyl starch was determined by potentiometric titration to ensure that the final degree of substitution reached 1.

[0119] S103. After the etherification reaction is complete, add 95% ethanol to the system, stir for 10 min, and let stand for 40 min to precipitate carboxymethyl starch. Filter to separate the precipitate, and wash with 70% ethanol until no Cl is found in the washing solution.- Then, after vacuum drying at 65°C for 6 hours, it was pulverized and passed through an 80-mesh sieve to obtain powdered carboxymethyl starch.

[0120] S104. Prepare a chitosan acetic acid solution with a concentration of 50 g / L by using a 2% (w / w) acetic acid solution.

[0121] The powdered carboxymethyl starch was prepared into a carboxymethyl starch aqueous solution with a concentration of 100 g / L using deionized water.

[0122] Sodium persulfate was prepared into an initiator solution of 75 g / L using deionized water;

[0123] A carboxymethyl starch aqueous solution was added to a four-necked flask, and the temperature was raised to 60°C at 200 rpm. Then, chitosan acetic acid solution was added dropwise at a rate of 4 mL / min. After the addition was complete, the mixture was stirred for 35 min. Then, initiator solution was added dropwise at a rate of 1.5 mL / min. After the addition was complete, the temperature was raised to 70°C, and the mixture was stirred for 3 h to carry out the grafting reaction. After the reaction was completed, the reaction solution was poured into 95% ethanol, and a precipitate was formed. After standing for 1 h, the precipitate was filtered, collected, washed three times with 70% ethanol, and then vacuum dried at 60°C for 8 h. The precipitate was then pulverized and passed through a 60-mesh sieve.

[0124] S2. The supernatant after settling in S1 is introduced into a reactor containing a composite catalyst, and ozone and trace amounts of H2O2 are introduced. The amount of ozone added is 60 mg / L, and the amount of trace amounts of H2O2 added is 30 mg / L. Catalytic oxidation is carried out at 35°C for 55 min.

[0125] The ozone dosage is 60 mg / L, and the trace H2O2 dosage is 30 mg / L;

[0126] The preparation of the composite catalyst includes the following steps:

[0127] S201, Mesoporous γ-Al2O3 support (particle size 0.5~1mm, specific surface area 200~280m²) 2 / g, mesopore size 5~12nm, purity ≥99%) was added to the plasma treatment instrument, using air medium, power 150W, vacuum degree -0.06MPa, and treatment for 20min. The treated support was then placed in a 110℃ forced-air drying oven and dried for 3.5h to obtain the activated support.

[0128] S202. Lanthanum nitrate was added to deionized water and stirred at 45°C until completely dissolved to obtain a La impregnation solution. Using the equal volume impregnation method, 1 / 3 of the above activated support was taken and the La impregnation solution was added dropwise to the activated support at a liquid-solid ratio of 1:1. After standing at room temperature for 2.5 h, the solution was dried at 60°C for 2.5 h to obtain the La-loaded support precursor.

[0129] S203. Copper nitrate and manganese nitrate were added to deionized water and stirred at 50°C until completely dissolved to obtain a Cu-Mn mixed impregnation solution. Using the equal volume impregnation method, the Cu-Mn mixed impregnation solution was added dropwise to the remaining 2 / 3 mass of the mixture of activated support and La-loaded support precursor at a liquid-solid ratio of 7:6, while stirring (120 rpm). After the addition was completed, the mixture was allowed to stand at room temperature for 3.5 h to obtain the Cu-Mn-La / γ-Al2O3 support precursor.

[0130] Total metal loading 10%, Cu:Mn:La = 3:2:1;

[0131] S204. Melamine was added to deionized water at a solid-liquid ratio of 1:14 and stirred at 85°C for 1 hour to obtain a suspension. The above Cu-Mn-La / γ-Al2O3 support precursor was added to the suspension, stirred at 55°C for 2 hours, dried at 60°C for 2 hours, and then dried at 90°C for 4 hours.

[0132] S205, after drying, is placed in a muffle furnace and heated to 200℃ at a rate of 2℃ / min under air atmosphere, and held at that temperature for 1 hour. Then, it is heated to 350℃ at a rate of 3℃ / min and held at that temperature for 2.5 hours. Next, it is heated to 480℃ at a rate of 4℃ / min and held at that temperature for 3.5 hours. Finally, it is cooled to a constant temperature at a rate of 5℃ / min and ground until the particle size is 1 mm.

[0133] S3. Introduce the oxidized wastewater into a fixed-bed bioreactor, fill it with immobilized bacterial agent, and carry out immobilized biological treatment. Control the temperature at 35℃ and the hydraulic retention time at 8h.

[0134] The method for preparing the immobilized bacterial agent is as follows: a mixture of Pseudomonas and Bacillus bacteria is immobilized on a porous foam carrier, with a viable cell density of 10⁻⁶. 10 CFU / g.

[0135] Specifically:

[0136] S302 The polyurethane foam is washed sequentially with anhydrous ethanol and sterile water, then soaked in 0.1 mol / L hydrochloric acid solution for 2.5 h, then soaked in 0.1 mol / L sodium hydroxide solution for 2.5 h, and finally rinsed with sterile water until neutral. After that, it is autoclaved at 121 °C for 30 min and dried at 50 °C to constant weight for later use.

[0137] S302. Pseudomonas putida and Bacillus subtilis were activated to OD600=1.5 and OD600=1.2 respectively using LB modified medium (containing 2g / L phenol). The two bacterial solutions were then mixed at a volume ratio of 3:2 and stirred evenly to obtain a mixed bacterial solution.

[0138] S303. Add the polyurethane foam treated in step S301 to the mixed bacterial solution at a solid-liquid ratio of 1:5. Shake and adsorb at 30°C and 120 rpm for 2.5 hours. Pour off the supernatant, add fresh mixed bacterial solution, transfer to a vacuum drying oven, and let stand at -0.06 MPa and 28°C for 1.5 hours. Take out the polyurethane foam and let it drain naturally.

[0139] S304. Dissolve sodium alginate in sterile water, stir at 60°C until dissolved, cool and add calcium chloride, stir until completely dissolved to obtain a crosslinking solution. The concentration of sodium alginate is 2% and the concentration of calcium chloride is 5%. Immerse the polyurethane foam adsorbed in step S303 into the crosslinking solution, let it stand at 25°C for 40 minutes, rinse with sterile water for 3 minutes, and then dry it at 60°C for 1 hour.

[0140] S305. Then place in a sterile incubator, add LB modified medium (containing 2 g / L phenol), and incubate at 28°C for 56 hours. During this period, replace the medium with fresh medium every 12 hours, and monitor the viable cell density by plate counting until it reaches 10⁻⁶. 10 CFU / g;

[0141] S4. Pass the biologically treated effluent into an activated carbon adsorption column. After adsorption saturation, elute with dilute ethanol. The activated carbon particle size is 1 mm, the adsorption flow rate is 2 BV / h, and the elution ethanol concentration is 5%. Evaporate the eluent to obtain salicylic acid crystals.

[0142] Comparative Example 1

[0143] Compared with Example 2, Comparative Example 1 replaces the composite flocculant in step S1 with an equal amount of traditional flocculant combination (polyaluminum chloride 120 mg / L + anionic polyacrylamide 30 mg / L), while the other steps are the same as in Example 2.

[0144] Comparative Example 2

[0145] Compared with Example 2, Comparative Example 2 omits the composite catalyst and H2O2 in step S2 and replaces it with ozone oxidation alone, increasing the ozone dosage to 80 mg / L. The other steps are the same as in Example 2.

[0146] Comparative Example 3

[0147] Compared with Example 2, Comparative Example 3 replaces the immobilized bacterial agent in step S3 with an equal volume of ordinary activated sludge (taken from the aerobic section of an urban wastewater treatment plant, with an MLSS of approximately 4000 mg / L), while the other steps are the same as in Example 2.

[0148] Comparative Example 4

[0149] Compared with Example 2, this Comparative Example 4 omits step S4, while the other steps are the same as in Example 2.

[0150] Experimental tests were conducted using the same batch of salicylates production wastewater. The initial indicators were: COD = 5200±100mg / L, total cyanide = 210±5mg / L, total SS = 850±20mg / L, total nitrogen = 180±5mg / L, and B / C ratio = 0.12.

[0151] The test results are shown in Table 1 below.

[0152] Table 1

[0153] S1 S2 S3 S4 SS removal rate (%) COD removal rate (%) Total cyanide removal rate (%) COD without water (mg / L) Total nitrogen removal rate (%) Salicylic acid recovery rate (%) Example 1 92.1 90.3 95.2 85.6 82.3 75.2 Example 2 93.8 91.7 96.5 72.4 85.1 78.6 Example 3 95.2 91.5 96.9 73.5 86.2 79.5 Comparative Example 1 80.5 80.2 88.7 125.3 70.2 76.1 Comparative Example 2 93.5 74.8 82.3 186.7 65.8 68.3 Comparative Example 3 93.6 91.5 96.3 158.2 58.7 77.9 Comparative Example 4 93.7 91.6 96.4 71.8 84.9 -

[0154] As shown in Table 1 above, compared with the comparative example, the processes in Examples 1-3 can achieve an SS removal rate of ≥92%, a total COD removal rate of ≥98%, a total cyanide removal rate of ≥95%, and a salicylic acid recovery rate of ≥75%, demonstrating significant effects on the treatment of wastewater from salicylic nitrile production.

[0155] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A process for the treatment of wastewater from the production of salicylanilide, characterized in that, It comprises the following steps: S1, the salicylonitrile production wastewater is first adjusted to pH 8.2~8.8, then the composite flocculant is added and stirred, and then the static precipitation is carried out; S2, the supernatant after the static precipitation in S1 is introduced into the reactor provided with the composite catalyst, ozone and trace H2O2 are introduced, and the catalytic oxidation reaction is carried out; S3, the oxidized wastewater is introduced into the fixed bed biological reactor filled with immobilized bacteria agent, and the immobilized biological treatment is carried out; S4, the biological treatment effluent is introduced into the activated carbon adsorption column, and after the adsorption saturation, the elution is carried out with dilute ethanol, and the salicylic acid crystal is obtained by evaporation crystallization of the eluate.

2. The process for treatment of wastewater from salicylanilide production according to claim 1, characterized in that, The NaOH or Na2CO3 used for adjusting pH in step S1; The stirring speed is 150~200rpm, and the stirring time is 20~30min.

3. The process as claimed in claim 1, wherein the process is characterized by, The adding amount of the composite flocculant in step S1 is 150~200mg / L, and the preparation method of the composite flocculant is as follows: the carboxymethyl starch aqueous solution is added into a four-necked flask, heated to 55~60℃ under the condition of 150~200rpm, then the chitosan acetic acid solution is added dropwise at a speed of 3~4mL / min, after the dropwise addition is completed, the stirring is continued for 30~35min, then the initiator solution is added dropwise at a speed of 1~1.5mL / min, after the dropwise addition is completed, the temperature is raised to 65~70℃, and the grafting reaction is carried out under the condition of temperature and stirring for 2.5~3h, after the reaction is completed, the reaction liquid is poured into 95% ethanol, the precipitate is separated out, after standing for 1h, the filtration is carried out, the precipitate is collected, washed with 70% ethanol for 2~3 times, then vacuum dried at 55~60℃ for 6~8h, and the powder is crushed through a 60 mesh sieve; The volume ratio of the carboxymethyl starch aqueous solution, the chitosan acetic acid solution and the initiator solution is 50:33:

1.

4. The process as claimed in claim 3, wherein the process is characterized by, The preparation of the carboxymethyl starch aqueous solution comprises the following steps: (1) according to the solid-liquid ratio of 1:2~3, the corn starch is added into 95% ethanol, uniformly dispersed at 100~150rpm, then the NaOH solution with a mass fraction of 20% is added dropwise, the volume ratio of the NaOH solution and the ethanol is 1:2~3, after the dropwise addition is completed, the temperature is raised to 30~35℃, the stirring is carried out under the condition of temperature for 1.5~2h, then the chloroacetic acid ethanol solution is added dropwise, the dropwise addition amount of the chloroacetic acid ethanol solution is 0.16~0.2 times of the total volume of the NaOH solution and the ethanol solution, after the dropwise addition is completed, the temperature is raised to 55~60℃, and the etherification is carried out under the condition of temperature and stirring for 3~4h; (2) After the etherification reaction is completed, 95% ethanol is added to the system, stirred for 10 min, and then allowed to stand for 30-40 min. The carboxymethyl starch precipitate is separated by suction filtration, washed with 70% ethanol until there is no Cl in the washing liquid, and then dried at 60-65°C under vacuum for 4-6 h. The powder is crushed to pass through an 80-mesh sieve to obtain a powdery carboxymethyl starch. - After the etherification reaction is completed, 95% ethanol is added to the system, stirred for 10 min, and then allowed to stand for 30-40 min. The carboxymethyl starch precipitate is separated by suction filtration, washed with 70% ethanol until there is no Cl in the washing liquid, and then dried at 60-65°C under vacuum for 4-6 h. The powder is crushed to pass through an 80-mesh sieve to obtain a powdery carboxymethyl starch. (3) the above powder-like carboxymethyl starch is prepared into a carboxymethyl starch aqueous solution with a concentration of 100g / L with deionized water for standby.

5. The process as claimed in claim 3, wherein the process is characterized by, The preparation method of the chitosan acetic acid solution is as follows: the chitosan is added into the NaOH solution with a mass fraction of 40%, stirred and treated in a constant temperature water bath at 80~85℃ for 4~6h, after the treatment, washed with deionized water until neutral, and vacuum dried at 60~65℃ until the constant weight to obtain refined chitosan; the refined chitosan is prepared into a chitosan acetic acid solution with a concentration of 50g / L with the acetic acid solution with a mass fraction of 2%.

6. The process as claimed in claim 3, wherein the process is characterized by, The preparation method of the initiator solution is as follows: the sodium persulfate is prepared into an initiator solution with a concentration of 60~75g / L with deionized water.

7. The process as claimed in claim 1, wherein the process is characterized by, The preparation of the composite catalyst in step S2 comprises the following steps: S201, mesoporous γ-Al2O3 carrier is added into a plasma treatment instrument, air medium is adopted, power is 150W, vacuum degree is -0.06MPa, treatment is carried out for 15-20min, the treated carrier is placed in a 100-110℃ air drying oven and dried for 2.5-3.5h to obtain an activated carrier; S202, lanthanum nitrate is added into deionized water, stirring is carried out at 40-45℃ until complete dissolution to obtain a La impregnation solution, 1 / 3 mass of the activated carrier is taken, the La impregnation solution is added dropwise into the activated carrier according to a liquid-solid ratio of 1:1, the mixture is placed at room temperature for 1.5-2.5h, and then air drying is carried out at 60℃ for 2-2.5h to obtain a La-loaded carrier precursor; S203, copper nitrate and manganese nitrate are added into deionized water, stirring is carried out at 45-50℃ until complete dissolution to obtain a Cu-Mn mixed impregnation solution, the Cu-Mn mixed impregnation solution is added dropwise into a mixture of the remaining 2 / 3 mass of the activated carrier and the La-loaded carrier precursor according to a liquid-solid ratio of 7:6, stirring is carried out during dropwise addition, the mixture is placed at room temperature for 3-3.5h to obtain a Cu-Mn-La / γ-Al2O3 carrier precursor; Total metal loading is 8-10%, Cu:Mn:La=3:2:1; S204, melamine is added into deionized water according to a solid-liquid ratio of 1:12-14, stirring is carried out at 80-85℃ for 1h to obtain a suspension, the Cu-Mn-La / γ-Al2O3 carrier precursor is added into the suspension, stirring is carried out at 50-55℃ for 1-2h, drying is carried out at 60℃ for 1.5-2h, and then drying is carried out at 90℃ for 3-4h; S205, after drying, the mixture is placed in a muffle furnace, air atmosphere is adopted, the temperature is raised to 200℃ at a rate of 2℃ / min, constant temperature is maintained for 1h, the temperature is raised to 350℃ at a rate of 3℃ / min, constant temperature is maintained for 2.5h, the temperature is raised to 480℃ at a rate of 4℃ / min, constant temperature is maintained for 3.5h, and finally the temperature is lowered to constant temperature at a rate of 5℃ / min, and grinding is carried out until the particle size is 0.5-1mm.

8. The process as claimed in claim 1, wherein the process is characterized by, The ozone addition amount in step S2 is 50-60mg / L, and the trace H2O2 addition amount is 20-30mg / L; The catalytic oxidation time is 45-55min, and the reaction temperature is 25-35℃.

9. The process as claimed in claim 1, wherein the process is characterized by, The method for preparing the immobilized bacterial agent in step S3 is: mixing Pseudomonas and Bacillus to immobilize on a porous foam carrier, and the viable bacterial density is 10 9 ~10 10 CFU / g; The temperature during the immobilized biological treatment is controlled to be 25-35℃, and the hydraulic retention time is 6-8h.

10. The process as claimed in claim 1, wherein the process is characterized by, The activated carbon particle size filled in the activated carbon adsorption column in step S4 is 0.5-1mm, the adsorption flow rate is 1-2BV / h, the elution ethanol concentration is 35%, and the eluent is evaporated and crystallized to obtain salicylic acid crystals.